Financial Literacy, Risk Perception, and Entrepreneurial Decision-Making among Young Entrepreneur in Indonesia - Thalib, Najdah; Suryaningrum, Diah Hari; Prakoso, Aryo; Hakim, Hakim (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the influence of financial literacy and risk perception on entrepreneurial decision-making among young entrepreneurs in Indonesia. As youth entrepreneurship continues to expand and contribute to national economic development, understanding the cognitive and behavioral factors that drive entrepreneurial decisions becomes essential. Using a quantitative approach with a sample of 150 young entrepreneurs aged 18–35, data were collected through a structured online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that both financial literacy and risk perception significantly and positively influence entrepreneurial decision-making. Financial literacy is identified as the strongest predictor, highlighting the importance of financial capability in shaping rational and strategic business decisions. Moreover, risk perception not only directly affects decision-making but also indirectly influences it through financial literacy, indicating partial mediation. These findings underscore the critical role of strengthening financial knowledge and risk awareness among young entrepreneurs to enhance their decision-making effectiveness and business sustainability. This study provides important implications for policymakers, educational institutions, and entrepreneurship development programs aiming to support the growth and resilience of youth-led enterprises in Indonesia.